Nanofilms: Biphasic Supramolecular Self‐Assembly of Ferric Ions and Tannic Acid across Interfaces for Nanofilm Formation (Adv. Mater. 28/2017). Issue 28 (July 2017) - Kim, Beom Jin; Han, Sol; Lee, Kyung‐Bok; Choi, Insung S.
Abstract : Nanofilm formation of supramolecular ferric ion (Fe III )‐tannic acid (TA) complexes across interfaces is reported by Insung S. Choi and co‐workers in article number1700784 . Fe III (red sphere) in one phase makes a contact with TA (blue drop) in the other phase and rapidly forms the Fe III ‐TA film (violet layer) at the interface of the two immiscible phases.